Applied statistics for engineers - Hogg, Robert V. (Macmillan, 1992)
Written by two of the leading figures in statistics, this highly regarded volume thoroughly addresses the full range of required topics: Provides early discussed fundamental concepts such as variability, graphical representation of data, and randomization and blocking in design of experiments. Provides a thorough introduction to descriptive statistics, including the importance of understanding variability, representation of data, exploratory data analysis, and time-sequence plots. Explores principles of probability, probability distributions, and sampling distribution theory.